Memory and Presence of Female Saints in Ksar El Kebir (Morocco) : Oral Transmission and Written Tradition - Hour, Rachid El, (Studies in the History and Society of the Maghrib ;, 2022)
This book discusses hagiographical sources from Morocco taking in consideration the often-overlooked oral tradition. Orality, as is shown in this study, completes and enriches the vision of hagiography that written sources traditionally has offered. The most relevant example in this book is the high presence of female saints in oral narratives that were not included in any other written sources. Recovering oral tradition to study hagiography as well as the role of female saints in Morocco has been one of the main areas of focus in this study as well as problematizing the dependence and dialogue between written and oral culture and can help to understand the diffusion and presence of similar phenomena in other areas of Morocco.